The contribution of perceptual and cognitive skills in anticipation performance of elite and non-elite soccer players - Martins, F; Garganta, J.; Oliveira, J.; Casanova, F. (International Journal of Sports Science, 2014)
The purpose of the present study is to examine the contribution of perceptual and cognitive processes in anticipation performance of soccer players under low- and high-intensity exercise demands. Eight elite and eight non-elite players completed a soccer-specific protocol, while simultaneously viewing dynamic and realistic filmed simulations of a soccer game. Anticipation, gaze behaviours, and retrospective reports were assessed. Results indicated that elite players were more accurate in anticipation performance. Under low-intensity, gaze behaviours exhibited by elite players accounted for a significant association in performance, whereas non-elite performance was significant related with cognition and evaluation statements. Under high-intensity, evaluation and deep planning verbalizations had a significant influence on elite group performance; in contrast, cognition statements was the only process-tracing measure that contributed significantly with non-elite performance.These findings indicated that the superior performance of elite players was associated with the selectivity of the perceptual and cognitive resources according to low- and high-intensity demands, respectively.